2015
DOI: 10.1177/1534734615598421
|View full text |Cite
|
Sign up to set email alerts
|

Using a Contradictory Approach to Treat a Wound Induced by Hematoma in a Patient With Antiphospholipid Antibody Syndrome Using Negative Pressure Wound Therapy

Abstract: A 48-year-old woman with antiphospholipid syndrome (APS) had multiple skin necrosis caused by massive bleeding and hematoma collection at the right lower leg, left thigh, and abdomen. During the first month, we did surgical debridement every 2 to 3 days with meticulous coagulation and applied negative pressure wound therapy (NPWT). Then as the base showed initial granulation, we changed the NPWT every 4 days. NPWT was used with lower pressure and cyclic mode (-40 to -75 mm Hg) to minimize trauma and to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Patients received various anticoagulants for a variety of concurrent comorbidities, including enoxaparin, warfarin and heparin medications. In two of the single case studies , the patients had concurrent antiphospholipid syndrome. In the case study reported by Ocampo , the patient under review had deep vein thrombosis (DVT), whilst the patient described by Malli was prescribed anticoagulants for prophylaxis of DVT.…”
Section: Resultsmentioning
confidence: 99%
“…Patients received various anticoagulants for a variety of concurrent comorbidities, including enoxaparin, warfarin and heparin medications. In two of the single case studies , the patients had concurrent antiphospholipid syndrome. In the case study reported by Ocampo , the patient under review had deep vein thrombosis (DVT), whilst the patient described by Malli was prescribed anticoagulants for prophylaxis of DVT.…”
Section: Resultsmentioning
confidence: 99%
“…The surgery of diabetic foot complications comprises a wide range of interventions, from incisions, debrides, transfalangeal and transmetataral amputations of toe/s or major amputations. Adjunctive treatments, such as: plastic surgery methods for the coverage of skin defects, negative pressure therapy and hyperbaric oxygenotherapy, both with the role of accelerating the process of wound granulation, represent methods that balance the evolution to healing (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Every year in the world, complications of DM become the cause of death in 1.6 million people, and, according to experts, this figure will double in 10 years (Bordianu et al, 2018). Approximately 25% of diabetics are at risk of developing diabetic foot ulcer (DFU), which is the main reason for their hospitalisation, which costs the US 40,000 dollars per event (Ray et al, 2005;Armstrong et al, 2017;Jang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%